1960
DOI: 10.4141/cjps60-006
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Relationship Between the Amount of Bloom and Yield of Apples

Abstract: The fruit yield of apple trees per unit area of trunk cross-section is shown to be very closely related to the author's estimate of the amount of bloom. Trees with maximum bloom score produced 46.48 kilograms of fruit per 100 square cm. of trunk cross-section, and lower percentages of bloom showed a linear relationship between the amount of bloom and yield of fruit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1963
1963
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…In mature trees, alternate bearing typically results from poor flower induction during a heavy cropping year (Westwood, 1993) with resultant poor flowering and light cropping the following year. Longley (1960) assessed the relationship between bloom and yield in mature apple trees of several varieties over a 10-year period. He reported a strong linear relationship between bloom intensity and cropping, with very low yields on trees with little bloom.…”
Section: Light Flowering That Limits Croppingmentioning
confidence: 99%
See 1 more Smart Citation
“…In mature trees, alternate bearing typically results from poor flower induction during a heavy cropping year (Westwood, 1993) with resultant poor flowering and light cropping the following year. Longley (1960) assessed the relationship between bloom and yield in mature apple trees of several varieties over a 10-year period. He reported a strong linear relationship between bloom intensity and cropping, with very low yields on trees with little bloom.…”
Section: Light Flowering That Limits Croppingmentioning
confidence: 99%
“…The economic disadvantages of excessive cropload have led to considerable research on fruit thinning and widespread commercial application of this practice. In apple, it has been demonstrated that croploads continue to increase even as flowering increases to very high levels (Longley, 1960). Clearly, excessive flowering contributes to the problem of excessive cropping and small fruit size.…”
Section: Excessive Flowering That Produces Excessive Crops Small Frumentioning
confidence: 99%